Strategi Ekspor Tekstil dan Produk Tekstil PT. Sri Rejeki Isman ke Amerika Serikat di Masa Pandemi COVID-19 - Tenriola, Andi; Tas'an, Ayu Kartika Julianingsih (Universitas Bosowa, 2024)
This research aims to analyze various export strategies of Indonesian textile and textile products (TPT) to the United States carried out by PT. Sri Rejeki Isman Tbk (Sritex) during the Covid-19 pandemic. This study uses a literature research method by analyzing various literature related to the export of textile and textile products by PT. Sritex. The results of this research show that Sritex utilizes various strategies to maintain and increase its product exports to the United States amidst the pandemic. Strategies used include product differentiation, low costs, product line focus, fiscal incentives from the government, textile 4.0 road map, production capacity enhancement, production process planning system improvement, approach to target countries, commodity determination, and increased engagement through E-commerce. Despite facing significant challenges due to the pandemic, Sritex successfully maintained its market share of TPT in the United States. This research refers to the theory of competitive advantage by Michael E. Porter to ensure the company's success in facing changing global market challenges during the Covid-19 pandemic. Additionally, this study provides recommendations for other TPT companies planning to expand their export markets to the United States and other countries during uncertain times due to global uncertainty challenges.